Cảnh quan và bộ mặt tộc người - Nguyễn, Từ Chi; Bùi, Xuân Đính; Nguyễn, Quốc Hùng; Nguyễn, Quang Huy; Nguyễn, Duy Thiệu (Đại học Quốc gia Hà Nội, 2023)
Gồm các bài viết nghiên cứu về đặc điểm cảnh quan và tộc người ở Việt Nam.